Analysis of performance and energy efficiency of processors with hybrid architecture - Dawid Żytko; Marcin Badurowicz (Journal of Computer Sciences Institute)
This study presents a comprehensive comparison of the performance and energy efficiency of performance (P) cores and efficiency (E) cores in Intel's 12th and 13th generation processors, including both desktop and mobile variants. The results demonstrate that P-cores are 1.3 to 3.2 times faster than E-cores, with the largest performance gaps observed in floating-point intensive tasks. E-cores show up to 17% better energy efficiency compared to P-cores in memory-intensive tasks, while P-cores demonstrate up to 2.1 times better energy efficiency in floating-point intensive calculations.